2018
DOI: 10.1051/ctv/20183302102
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic composition and total antioxidant capacity analysis of red wine vinegars commercialized in Portuguese market

Abstract: SUMMARYIn the last years, there has been an increase in consumption of wine vinegars in Portugal. Thus, the aim of this work was to evaluate the phenolic composition and total antioxidant capacity from several commercial red wine vinegars commercialized in Portuguese market. Several parameters were evaluated: general phenolic composition, chromatic characteristics, individual anthocyanins and phenolic acids by HPLC, and total antioxidant capacity by two methodologies (DPPH and ABTS). For the different paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
1
7
1
1
Order By: Relevance
“…The antioxidant capacity expressed by the ABTS assay determined in this study is similar to those reported by Arvaniti et al [3] for commercial and homemade Greek vinegars, by Cruz et al [8] for red wine vinegars and by Li et al [15] for apple vinegar, persimmon vinegar and kiwifruit vinegar. As seen in Table 3, the DPPH values increased from 17.81±1.91% to 31.35±2.77% for the vinegars obtained from raspberries, from 26.92±0.53% to 39.65±2.70% for the variants obtained from blackberries and from 36.41±1.11% to 49.90±2.12% for the variants obtained from blueberries.…”
Section: The Antioxidant Capacity Of Vinegarsupporting
confidence: 90%
“…The antioxidant capacity expressed by the ABTS assay determined in this study is similar to those reported by Arvaniti et al [3] for commercial and homemade Greek vinegars, by Cruz et al [8] for red wine vinegars and by Li et al [15] for apple vinegar, persimmon vinegar and kiwifruit vinegar. As seen in Table 3, the DPPH values increased from 17.81±1.91% to 31.35±2.77% for the vinegars obtained from raspberries, from 26.92±0.53% to 39.65±2.70% for the variants obtained from blackberries and from 36.41±1.11% to 49.90±2.12% for the variants obtained from blueberries.…”
Section: The Antioxidant Capacity Of Vinegarsupporting
confidence: 90%
“…When comparing the quality characteristics and chemical composition of the examined vinegars, a great diversity was observed in the obtained values. It is well known that various factors such as production methods, raw materials (grape, apple, pomegranate, rose petals), storage conditions, wood contact and aging period can affect the physicochemical composition and sensory properties of vinegars and contribute to the final quality of vinegars (Budak et al, 2010;Cruz et al, 2018;Ho et al, 2017;Xia et al, 2018). In Table 1, the physicochemical properties of 18 different examined vinegar samples are presented, while their organic acid and sugar contents are summarized in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…In a few recent studies, spectrophotometric and chromatographic techniques have been used to investigate the bioactive compounds, volatile composition and antioxidant capacity of different types of vinegar (Barnaba et al, 2015;Budak et al, 2010;Cruz et al, 2018;Kelebek et al, 2017;Ubeda et al, 2011;Yu et al, 2012). However, little data has been published so far, while a characterization of vinegars in the Greek market has not been extensively studied (Lalou et al, 2015;Sinanoglou et al, 2018) and a comparison of them with homemade vinegars has not been conducted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spośród kwasów fenolowych odnotowano również występowanie kwasu prokatechinowego, chlorogenowego, kawowego, syryngowego, p-kumarowego oraz hydroksycynamonowego. W badanych próbach kwas syrygenowy oraz kawowy były kwasami fenolowymi występującymi w największych ilościach (odpowiednio 5,17 mg/L oraz 3,43 mg/L) [99]. Badania I. Ozturk i wsp.…”
Section: Właściwości Antyoksydacyjne Octówunclassified